Conservation Practice Values in Museology and History of Tourism Courses Through Experiential-Based Learning Methods - Yuliantri, Rhoma Dwi Aria (Universitas PGRI Yogyakarta, 2022)
This research aims to analyze the learning values on the topic of conservation in the Museology Course, Department of History Education, Yogyakarta State University. The learning model that is used is experiential-based learning, which is shaped by students' learning through direct reflection. The research method used is a descriptive qualitative research method conducted in the Museology and History of Tourism class, Department of History Education, Yogyakarta State University in 2021-2022 and Tata Kelola ISI Yogyakarta in Anak Bajang Museum. The results showed that experiential-based learning is a suitable method for learning museology with the theme of conservation. The reason for students in general is that direct practice provides direct experience so that conceptual understanding can be put into practice. The values obtained by students are having discipline, thoroughness, responsibility, cooperation, and patience, which are obtained when practicing and treating the diversity that is conserved. In addition, students also increase their care for historical heritage.